2021
DOI: 10.1002/admi.202101593
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose and Its Interface: On the Road to the Design of Emerging Materials

Abstract: The interest in the hierarchical structure, the multi-scale organization, and the properties of cellulose has long been the prerogative of botanists and plant physiologists. The last decade has witnessed the potential of a top-down approach to take apart cellulose-based raw materials into their micro-and nano-sized building blocks and to use them to design and fabricate functional materials and devices with new and, in some cases, outstanding properties. At present, cellulose is not only one of the main consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 226 publications
0
10
0
Order By: Relevance
“…The accessibility of cellulose chains to water is governed by the availability of hydroxy groups on the surface of a cellulose crystal. While cellulose–cellulose hydrogen bonds often take precedence over cellulose–water hydrogen bonds (hence the insolubility of cellulose in water), there is also an abundance of hydroxy groups on the crystallite surface that have the propensity to hydrogen bond with water . A common method by which to quantify the availability of hydroxy groups in cellulosic materials is to substitute the hydrogen in available hydroxy groups for deuterium through a water/deuterium oxide (H–D) solvent exchange .…”
Section: Fundamentals Of Cellulose– and Nanocellulose–water Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accessibility of cellulose chains to water is governed by the availability of hydroxy groups on the surface of a cellulose crystal. While cellulose–cellulose hydrogen bonds often take precedence over cellulose–water hydrogen bonds (hence the insolubility of cellulose in water), there is also an abundance of hydroxy groups on the crystallite surface that have the propensity to hydrogen bond with water . A common method by which to quantify the availability of hydroxy groups in cellulosic materials is to substitute the hydrogen in available hydroxy groups for deuterium through a water/deuterium oxide (H–D) solvent exchange .…”
Section: Fundamentals Of Cellulose– and Nanocellulose–water Interactionsmentioning
confidence: 99%
“…While cellulose−cellulose hydrogen bonds often take precedence over cellulose−water hydrogen bonds (hence the insolubility of cellulose in water), there is also an abundance of hydroxy groups on the crystallite surface that have the propensity to hydrogen bond with water. 201 A common method by which to quantify the availability of hydroxy groups in cellulosic materials is to substitute the hydrogen in available hydroxy groups for deuterium through a water/deuterium oxide (H−D) solvent exchange. 202 The availability of hydroxy groups for solvent exchange is dependent on a number of factors: (i) their position in the cellulose chain (i.e., 2-, 3-, or 6-position), (ii) whether they are within the ordered or disordered region of the cellulose microfibril, and (iii) whether they are located on the surface or embedded within the crystallite (microfibril).…”
Section: Water and Nanocellulosementioning
confidence: 99%
“…14 We note that the nature of CNC surfaces is currently an active area of research. 32 A strong affinity of Mg 2+ and Ca 2+ for carboxylatefunctionalized CNCs was observed by Lombardo et al, 33 who studied the salt-induced aggregation of CNCs prepared via TEMPO-mediated oxidation. These authors found that the critical concentrations of MgCl 2 and CaCl 2 required to induce aggregation of the CNCs were the same within experimental error.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…Site-specific binding to the citrate moiety may also take place . We note that the nature of CNC surfaces is currently an active area of research …”
Section: Resultsmentioning
confidence: 99%
“…(c2, c5) Janus CNM particles with more hydrophobicity (water contact angle is >90°) will sink more into the oil phase. Reprinted with permission under a Creative Commons Attribution Attribution-NonCommercial 4.0 International License from ref . Copyright 2021 Wiley-VCH.…”
Section: Janus Cnm Particles and Their Applicationsmentioning
confidence: 99%